Comparison between stool antigen test and rapid urease test for Helicobacter pylori diagnosis in symptomatic cases of peptic ulcer disease at a tertiary care centre - Jha, Jyotish Chandra; Koirala, Puru; Shah, Ashish; Dhakal, Anish; Karna, Rohit Kumar; Budhathoki, Anu (Journal of Kathmandu Medical College, 2024)
Background: Peptic ulcer disease is defined as a breach in gastric epithelium of the inner lining of the gastrointestinal tract due to imbalance between destructive gastric acid, pepsin, and protective gastric mucosa. Helicobacter pylori (H. pylori) is a gram-negative, flagellated bacilli. H. pylori infection eradication is possible with antimicrobial therapy, so its prompt and appropriate diagnosis is very important. Objectives: To compare between the results of stool antigen test (SAT) and rapid urease test (RUT), with assessment of sensitivity and specificity. Methods: A hospital-based descriptive cross-sectional study in department of Internal Medicine at Birat Medical College and Teaching Hospital was conducted from 2023 January 2 to 2023 July 2 after institutional ethical clearance. Symptomatic gastritis patients visited in outpatient department, admitted and who gave consent were enrolled through consecutive sampling methods in this study. Biopsy sample obtained by upper gastrointestinal endoscopy of these patients were examined by RUT. ABON™ One Step H. pylori SAT Device was used for the detection of H. pylori antigens in the Stool Specimens obtained from these patients. Microsoft Excel sheet and SPSS v.23 were used for data analysis. Results: More than two-thirds (105, 67.7%) were positive in upper gastrointestinal endoscopy and nearly two-thirds (100, 64.5%) had positive stool antigen tests. Conclusion: This study showed the H. pylori stool antigen test is effective non-invasive way to find out H. pylori infection demonstrating no significant difference in specificity and sensitivity in comparison to RUT and can be considered as a routine diagnostic tool for surveying clinical significance as well as eradication of H. pylori.